Simulador radiográfico antropomórfico de mama humana - Silva, Eliano Soares da (2012)
Mammography is a diagnostic imaging method in which interpretation depends on knowledge of radiological aspects as well as the clinical exam and pathophysiology of breast diseases. In this work a mammography phantom was developed to be used for training in the operation of mammographic x-ray equipment, image quality evaluation, self-examination and clinical examination of palpation. Polyurethane was used for the production of the phantoms for its physical and chemical properties and because it is one of the components normally used in prostheses. According to the range of flexibility of the polyurethane, it was possible to simulate breasts with higher or lower amount of adipose tissue. Pathologies such as areolar necrosis and tissue rejection due to surgery reconstruction after partial mastectomy were also simulated. Calcifications and nodules were simulated using the following materials: polyethylene, poly (methyl methacrylate), polyamide, polyurethane and poly (dimethyl silicone). Among these, polyethylene was able to simulate characteristics of calcification as well as breast nodules. The results from mammographic techniques used in this paper for the evaluation of the phantoms are in agreement with data found in the literature. The image analyses of four phantoms indicated significant similarities with the human skin texture and the female breast parenchyma. It was possible to detect in the radiographic images produced regions of high and low radiographic optical density, which are characteristic of breasts with regions of different amount of adipose tissue. The stiffnesses of breast phantoms were adjusted according to the formulation of the polyurethane which enabled the production of phantoms with distinct radiographic features and texture similar to human female breast parenchyma. Clinical palpation exam of the phantoms developed in this work indicated characteristics similar to human breast in skin texture, areolar region and parenchyma